Digital Transformation in School Administration: Enhancing Correspondence and Archival Systems - M. Yasman Rahma Jaya; Riyuzen Praja Tuala; Devin Cumbuan Putri; Yosep Aspat Alamsyah (Al-Qalam Institue, 2026)
This study aims to analyze the management of administrative services in correspondence and records management and the role of information technology in supporting administrative effectiveness using a descriptive qualitative approach, with data collected through interviews, observations, and documentation and analyzed using the Miles and Huberman model; the findings indicate that correspondence and records management have been implemented systematically through processes of document receipt, recording, numbering, disposition, distribution, storage, security, classification, maintenance, retrieval, and retention, supported by a digital service system that enhances effectiveness, efficiency, accuracy, and security, although challenges such as increasing document volumes, limited storage capacity, and incomplete digitization remain; therefore, the study implies that strengthening digital administrative systems and accelerating records digitization are essential for improving the quality, accessibility, sustainability, and efficiency of administrative services.